MEASUREMENT OF MATHEMATICAL PROBLEM SOLVING ABILITY BASED ON SELF EFFICACY CATEGORIZATION USING MIXED METHODS APPROACH - Busnawir Busnawir; Mukhsar Mukhsar; Hidayat Ahmad; Kodirun Kodirun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Problem-solving ability is an important part of learning mathematics. The low ability to solve mathematics needs to get attention related to students' self-efficacy. This study aims to determine the level of mathematical problem-solving abilities based on the categorization of students' self-efficacy at high, medium, and low levels. This research was conducted in class XI SMAN 1 Konawe Utara with a total of 37 students as subjects. This type of research is descriptive quantitative and qualitative in the form of a mixed method. The research instrument consisted of tests of mathematical problem-solving skills, self-efficacy questionnaires, and interview guidelines. Data were analyzed using quantitative and qualitative descriptive analysis. The results of the study show that students with high self-efficacy are able to solve math problems following all stages of Polya; students with moderate self-efficacy are unable to follow all Polya stages, while students with low self-efficacy are unable to solve math problems following Polya stages. It was concluded that the level of self-efficacy of students had an influence on ability to solve math problems based on Polya's steps